Topical immunotherapy with diphenylcyclopropenone in paediatric patients with alopecia areata-A retrospective study of 97 patients - Farzad Esmaeili; Seyed Mohammad Vahabi; Mohammadsadegh Abdoli; Patrick Fazeli; Narges Ghandi; Leila Seddigh; Zeinab Aryanian; Ifa Etesami (Wiley, 2024)
Abstract Background Alopecia areata (AA) is an autoimmune disease causing chronic non‐scarring hair loss. Different therapeutic regimens have been suggested for AA, which depend on patients' age, scalp involvement extent and duration. Topical immunotherapy with diphenylcyclopropenone (DPCP) is one of the treatment options for these patients. Objectives We aimed to investigate the response to DPCP in paediatric AA patients. Methods This retrospective study included 97 paediatric AA patients followed in the DPCP clinic from March 2016 to March 2021 at a referral dermatology hospital. Results In a cohort of 97 paediatric patients with AA under treatment with DPCP, with a mean age of 11.10 ± 0.9, 53.6% of the patients were male. Patchy alopecia was the most prevalent type (45.4%). After 6 months of DPCP treatment, 51.5% showed no response, while 3.1% achieved complete response. At the 12‐month evaluation, among the 68 patients who continued treatment, complete response was observed in 8.8%. A significant positive correlation was found between alopecia type, specifically patchy, and treatment response (p = 0.031). Additionally, treatment duration emerged as a significant predictor of positive response at both six (OR 1.450, p = 0.026) and 12 months (OR 1.310, p = 0.043). A higher initial Severity of Alopecia Tool score was inversely correlated with treatment response (Spearman's rho −0.14, p = 0.002), indicating that initial disease severity may predict treatment efficacy. Conclusions One year after the onset of DPCP in paediatric AA patients, the complete response and any hair regrowth rates were 8.8% and 61.8%, respectively. The milder initial disease severity and longer duration of treatment resulted in a better response.